2011
DOI: 10.1017/s0008423911000151
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Dissent on the Supreme Court of Canada

Abstract: Abstract.While there is an extensive literature on the causes of dissensus on appellate courts in the US, few empirical studies exist of the causes of dissent in Canadian Supreme Court. The current study seeks to close that gap in the literature, proposing and then testing what we call a Canadian model of dissent. We find that the likelihood of dissent is strongly related to four broad factors that appear to exert independent influence on whether the Court is consensual or divided: political conflict, institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…An increase in workload has been found to be associated with a decrease in the dissent rate at the US Supreme Court (Epstein, Landes and Posner 2013) and the Australian High Court (Smyth 2004), with Epstein, Landes and Posner (2013) finding that a 10 percent increase in workload is correlated with about a three percent decline in the dissent rate. Other studies, however, have found no or only a weak association between workload and dissent rate in a number of countries (Walker, Epstein and Dixon 1988;Alarie and Green 2017;Songer et al 2011). The workload, and its relationship to the time a judge has at work, may also be related to his ability or willingness to tie a decision into prior decisions through finding and citing case law.…”
Section: The Judge As Rational Actormentioning
confidence: 99%
“…An increase in workload has been found to be associated with a decrease in the dissent rate at the US Supreme Court (Epstein, Landes and Posner 2013) and the Australian High Court (Smyth 2004), with Epstein, Landes and Posner (2013) finding that a 10 percent increase in workload is correlated with about a three percent decline in the dissent rate. Other studies, however, have found no or only a weak association between workload and dissent rate in a number of countries (Walker, Epstein and Dixon 1988;Alarie and Green 2017;Songer et al 2011). The workload, and its relationship to the time a judge has at work, may also be related to his ability or willingness to tie a decision into prior decisions through finding and citing case law.…”
Section: The Judge As Rational Actormentioning
confidence: 99%
“…Politics matter, judges strategize, but professional norms that restrict dissent and decry public 21 The extent to which a 5 percent dissent rate is high or low depends on the institutional context. See discussion by Shachar et al (1997) and Eisenberg et al (2011) for the case of Israel, Henderson (2007) for the case of the U.S. Supreme Court, Eisenberg and Miller (2009) for U.S. state supreme courts, Smyth and Narayan (2004) for the Australian High Court, and Songer et al (2011) for the Canadian Supreme Court. 22 On Japan, see Ramseyer andRasmusen (2003, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On Canada, see Tate and Sittiwong (), Alarie and Green (), Green and Alarie (), and Songer et al. (). On Germany, see Schneider () and Vanberg ().…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29 Similarly the 'realism' of the standards-based approach has been associated with consumer-welfarism, which in a result-orientated approach feeds in reasonableness to decision making at the cost of predictability. 34 A study of the Supreme Court of Norway found the odds of dissent increase by 79 per cent where a case involves any ECHR issue. These have shown there to be higher rates of dissent in civil liberties cases than in economic cases.…”
mentioning
confidence: 99%